Sources of Heavy Minerals of the Neogene Clastics at Bekhme, Northern Iraq - AL-Rawi, Saif Al-Ddin A.; Razzak , Suhad Khalaf A. (Iraqi Journal of Science, 2020)
Ten samples were collected from Injana and Mukdadiya Formations, representing 5 samples of fine grain sandstone (F) and 5 samples of very fine grain sandstone (VF). The heavy metals study showed that the opaque mineral recorded the highest percentage in comparison with other heavy metals. While, transparent minerals, including unstable minerals (Amphibole including Hornblend and Glaucophane) and (pyroxene including Orthopyroxene and Clinopyroxene), Metastable minerals including (Epidote, staurolite, Garnet, Kyanite) indicated metamorphic source, Ultrastable minerals (Zircon, Rutile, Tourmaline), Mica group (chlorite, biotite and muscovite). These accumulations indicate that the heavy minerals are derived from mafic igneous and metamorphic rocks mostly, as well as acidic igneous and reworked sediments. Ternary diagram of heavy metals stability showed that they are moderately stable due to the effect of the opaque mineral that have highest attention. Both sandstones for the Injana and Mukdadiya formations are derived from active continental margins. This source rocks may be represented by Taurus and Zagros Mountains.